Letteratura e psicoanalisi in Russia all'alba del XX secolo - Zalambani, Maria (Biblioteca di Studi Slavistici, 2022)
Psychoanalysis spread earlier and faster in Russia than in Western Europe. According to the author, there are three main reasons for this. First, psychoanalysis is based on the fictional structure of patients's narratives. In a literary-centric country such as Russia, the 'literary character' of psychoanalysis quickly attracts the Russian intelligentsia. Secondly, the formal similarities between literary and psychoanalytic language, and the close connection between the poetic word and the rhetoric of the unconscious, contribute to rendering Freudian language particularly familiar in Russia. Thirdly, the Silver Age, with its attention to the symbol, the 'other', and the double, contributes to increasing interest in the theory of the unconscious. This will continue until after the October Revolution as the state relies on psychoanalysis to help forge the new Soviet citizen. This 'alliance', however, is short-lived, and Freudian psychoanalytic theory will be ostracized from the 1930s up to the end of the Soviet regime.